Evaluating the effectiveness of GP endorsement on increasing participation in the NHS Bowel Cancer Screening Programme in England: study protocol for a randomized controlled trial. - Damery, S; Smith, S; Clements, A; Holder, R; Nichols, L; Draper, H; Clifford, S; Parker, L; Hobbs, R; Wilson, S (2012)
BACKGROUND: The success and cost-effectiveness of bowel cancer screening depends on achieving and maintaining high screening uptake rates. The involvement of GPs in screening has been found to improve patient compliance. Therefore, the endorsement of screening by GPs may increase uptake rates amongst non-responders. METHODS/DESIGN: A two-armed randomised controlled trial will evaluate the effectiveness of a GP endorsed reminder in improving patient participation in the NHS Bowel Cancer Screening Programme (NHSBCSP). Up to 30 general practices in the West Midlands with a screening uptake rate of less than 50% will be recruited and patients identified from the patient lists of these practices. Eligible patients will be those aged 60 to 74, who have previously been invited to participate in bowel screening but who have been recorded by the Midlands and North West Bowel Cancer Screening Hub as non-responders. Approximately 4,380 people will be randomised in equal numbers to either the intervention (GP letter and duplicate FOBt kit) or control (no additional contact) arms of the trial. The primary outcome measure will be the difference in the uptake rate of FOBt screening for bowel cancer between the intervention and control groups at 13 weeks after the GP endorsed reminder and duplicate FOBt kit are sent. Secondary outcome measures will be subgroup analyses of uptake according to gender, age and deprivation quartile, and the validation of methods for collecting GP, NHSBCSP and patient costs associated with the intervention. Qualitative work (30 to 40 semi-structured interviews) will be undertaken with individuals in the intervention arm who return a FOBt kit, to investigate the relative importance of the duplicate FOBt kit, reminder to participate, and GP endorsement of that reminder in contributing to individuals' decisions to participate in screening. DISCUSSION: Implementing feasible, acceptable and cost-effective strategies to improve screening uptake amongst non-responders to invitations to participate is fundamentally important for the success of screening programmes. If this feasibility study demonstrates a significant increase in uptake of FOBt screening in individuals receiving the intervention, a definitive, appropriately powered future trial will be designed. TRIAL REGISTRATION NUMBER: ISRCTN: ISRCTN86784060.